Villiers de L’isle-Adam’s “El Desdichado” - Domingos, Norma (Lettres Françaises, 2008)
The nervalian titled “El desdichado” (1867), by Villiers de l’Isle-Adam (1839-1888) depicts a project of the defi nitive version of “Souvenirs occultes” published in his book Contes cruels of 1883. Indeed, each stanza of the poem is revisited and developed in the elaboration of the poetic short story. Based on the analysis of “El desdichado” of Villiers, the purpose of this study is to present some general aspects about Villiers de l’Isle-Adam’s poetic language of the author, as well as the intertextuality with the poem of Gérard de Nerval’s homonym poem in Les Chimères in 1854.